Asuhan Keperawatan Pada Ny. E P3A0 Post Sectio Caesarea Dengan Indikasi Serotinus Di RS T IV Slamet Riyadi Surakarta - Yulianti, Siti Febtina, Winarsih Nur Ambarwati, S.Kep, Ns, ETN, M.Kep (2015)
Background: Sectio caesarea often found in hospital with the cause of one of them is serotinus, namely pregnancy lasting 42 weeks or more. Serotinus pregnancy is more common in young primigravida and old primigravida or on grandemultiparatis. Objective: To determine the client's nursing care on post sectio caesarea with serotinus indications include assessment, intervention, implementation, and evaluation of nursing. Results: After 3 x 24 hour nursing care for the results obtained, the client pain scale decreased from 7 to 2, no signs of infection occur, the milk can not be properly fulfilled. Conclusion: Cooperation between the health care team with the client / family is indispensable for the success of nursing care, therapeutic communication can encourage more cooperative clients, so the problem of nursing patients about pain, risk of infection, and the ineffectiveness of breastfeeding can be carried out in accordance with the intervention of good and most problems can be resolved. Keywords: sectio caesarea, serotinus, pain, risk of infection, ineffective breastfeeding